Pembelajaran Bahasa Jerman Berbasis Padlet sebagai Pemantik Motivasi Belajar Selama Pandemi - Fika Ristanti (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The purpose of writing this best practice is to impelement the use of padlets and find out the results and impact of using padlets on student’s motivation learning in German during the Covid-19 pandemic. The strategy used is using padlets. Padlet is a free online whiteboard app that has many advantages. By using padlets, teachers and students can upload and download various documents in the form of videos, photos, voice recordings, texts or other documents and can be updated at any time. Padlet is an atrractive medium and very easy to use. The method used in this best practice research is qualitative descriptive. Padlet is implemented to deliver “Familie, Wohnung, Essen und Trinken”material for class XI MIPA 1 and “Freizeit, Reisen, Tagesablauf der Lieblingsfiguren” material for class XII IPS 1, XII IPS 2 in the odd semester of the 2020/2021 school year (August-November) at SMAN 2 Wates. The steps in this implementation consist of the preparation, implementation and evaluation. The end of this best practice activity is that author gives a questionnaire to students regarding the evaluation of using padlets, which are then analyzed and used as basis for making conclusions. From the questionnaire, it was found more than 80% of students felt happy and interested in participating in distance learning when using padlet. More than 80% of students do assigments on time and more than 75% students no longer feel reluctant to ask questions or discuss with teachers or other students. The four indicators than used as author to make conclusion that padlet can increase students’ motivation learning to learn German during the Covid-19 pandemic.